Comunicación asertiva y el rendimiento académico de los estudiantes del sexto “A”, en la Escuela Miguel Riofrio, sección matutina, Loja 2021-2022. - Pacheco Lara, Juan Diego (2022)
The research is aimed at assertive communication and academic performance within the educational process, it is necessary to start from the problem where different factors that intervene in the learning results and pedagogical and personal causes have been evidenced. It is necessary to mention the general objective: To determine the incidence of assertive communication in the academic performance of students in the sixth grade of General Basic Education, parallel "A", morning section, of the "Miguel Riofrio" School in the city of Loja, period 2021-2022, The approach of the work was mixed, both qualitative and qualitative because it is a human group, from which reasons and aspects related to the topic and problem were explained, It was also quantitative because it allowed us to investigate the use of numerical data in order to systematize, organize and structure them, within this it was framed in a social sense that contemplates education, so that it is within the theoretical-descriptive research, where the relevance of assertive communication was sought to be specified, during the process the scientific, inductive, deductive, statistical and descriptive methods were applied, likewise, techniques such as direct observation, survey, initially allowed to collect the information product of an investigation and express the link through the practice between knowledge, In conclusion, it is remarkable the incorporation of assertive communication within the educational process because it intervenes in the integral formation of students, helps to improve academic performance and social relations. Key words: Assertive communication - Academic performance - Educational process - Social relationships - Learning.